Modeling, synthesis and design of radio frequency integrated square planar spiral inductor - 393691 Tee, Yeu Chen; Mazlina Esa (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2004